Report of the Evaluation Study on the Scheme "Modernization of Office Systems" - Planning Commission (Planning Commission, Government of India)
The Institute of Public Auditors of India (IPAI) is a registered society of professionals. Its main aim and objectives are to: Promote education in the disciplines of auditing, finance, accounting in public bodies. Suggest ways for effective accounting and auditing in the Central and State Governments, Public Enterprises, Public Institutions, Government aided voluntary organizations, local bodies and authorities.
Planning Commission, Government of India
Keywords: TECHNOLOGY